Religion and the Secular in Eastern Germany, 1945 to the Present. - Schmidt-Lux, Thomas (Studies in Central European Histories Ser., 2010)
The most common explanations view either the socialist past or larger scale processes of modernization to be the cause of eastern German secularization. The volume attempts to discover historically variable reconfigurations of religion and the secular at the local level.